MAKNA SIMBOLIK PADA TRADISI SEDEKAH BEDUSUN DI DESA PENANDINGAN KABUPATEN MUARA ENIM KAJIAN SEMIOTIK - Sinta Nopita Sari; Dessy Wardiah; Achmad Wahidy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the symbolic meaning contained in the tradition of sedekah bedusun in Penandingan Village, Muara Enim Regency based on Semiotic Studies. This type of research is qualitative research using descriptive method. The object of research is the symbolic meaning contained in the bedusun alms tradition in Penandingan Village, Muara Enim Regency. Data collection techniques using direct observation, interviews, recording, notes and documentation. This research was conducted in February 2025, the research subject is the symbols contained in the sedekah bedusun tradition. To test the validity of the data using triangulation. After analysis, there are eight symbolic meanings, each of which contains a certain meaning. Symbols that have deep meaning in the Sedekah Bedusun tradition in Penandingan Village, Muara Enim Regency.